Efectos del decreto legislativo N° 1086 en el nivel de cumplimiento de los Derechos Laborales en las empresas comercializadoras de vehículos menores del distrito de Tarapoto. Período 2010- 2011 - Cubas Hernández, Edison (2013)
In the present research aimed to determine the effects of Legislative Decree No. 1086 on the level of compliance with labor rights in smaller vehicles trading companies Tarapoto district. Period 2010 - 2011, in a population universe represented by companies engaged in the marketing of small vehicles in the district of Tarapoto and database SUNAT is ten (10) companies who type Applied research was applied, in order to get response solution to a problem and descriptive by obtaining data from a reality, the total trading companies smaller vehicles in the district of Tarapoto covered by the Legislative Decree No. 1086 - Database REMYPE eight (08) qualify and Micro Companies representing 80% and two (02) Small Business representing 20%, meanwhile, the total number of workers surveyed Microenterprise, three (03) responded that between 2010-2011 are hired indefinite period representing 12%, eleven (11) indicated having fixed-term contracts mean 42%, and twelve (12) reported not having any type of employment contract, accounting for 46%. In Small Business 01 worker said having a contract for an indefinite period which represents 9%, seven (07) responded be hired for a fixed term mean 58%-four (04) admit not be hired, accounting for 33%